2016
DOI: 10.2147/copd.s113176
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled corticosteroid normalizes some but not all airway vascular remodeling in COPD

Abstract: BackgroundThis study assessed the effects of inhaled corticosteroid (ICS) on airway vascular remodeling in chronic obstructive pulmonary disease (COPD).MethodsThirty-four subjects with mild-to-moderate COPD were randomly allocated 2:1 to ICS or placebo treatment in a double-blinded clinical trial over 6 months. Available tissue was compared before and after treatment for vessel density, and expression of VEGF, TGF-β1, and TGF-β1-related phosphorylated transcription factors p-SMAD 2/3. This clinical trial has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…This first study reporting anti‐EMT effects of ICS in COPD demonstrated marked reduction in EGFR, Rbm fragmentation, S100A4 and MMP‐9 expression in the active arm compared with placebo (Sohal et al, ), but Rbm hyper‐vascularity remained unchanged (Soltani et al, ). It is quite possible that a longer treatment by ICS may also affect Rbm hyper‐vascularity.…”
Section: Emt In Chronic Lung Diseasementioning
confidence: 99%
“…This first study reporting anti‐EMT effects of ICS in COPD demonstrated marked reduction in EGFR, Rbm fragmentation, S100A4 and MMP‐9 expression in the active arm compared with placebo (Sohal et al, ), but Rbm hyper‐vascularity remained unchanged (Soltani et al, ). It is quite possible that a longer treatment by ICS may also affect Rbm hyper‐vascularity.…”
Section: Emt In Chronic Lung Diseasementioning
confidence: 99%
“…This is the first clinical study to show the anti-EMT effects of ICS. We also observed effects on vascular remodelling in COPD patients (45), angiogenesis (46) is also major part of EMT when associated with the formation of pro-cancer stroma (47). In epidemiological studies, it is observed that ICS treatment of COPD patients significantly reduces lung cancer risk but the underlying mechanisms are not clear (48).…”
Section: Potential Emt Treatmentsmentioning
confidence: 69%
“…Other studies, including in vivo mouse models that replicate the pathologic features of EMT and fibrosis (81), and potentially exacerbations (82)(83)(84)(85)(86)(87)(88)(89)(90), could be valuable in elucidating mechanisms identifying therapeutic targets and test new therapies (91). Validation using combinations of in vivo and ex vivo human studies (45,(92)(93)(94)(95)(96) will provide powerful evidence for their roles and potential targeting in COPD (82,97). There could be wider implications for other lung diseases such as idiopathic pulmonary fibrosis (IPF) and lung cancer where EMT activity and fibrosis are prevalent (26,81,98).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported an increase in vessels in general, and VEGF and TGF-β1 positive vessels, in particular, in the reticular basement membrane (Rbm) of smokers and patients with COPD, they were also seen encroaching into the epithelium [182][183][184][185][186]. It is quite possible that these two growth factors actively promote neoangiogenesis of both the Rbm and the epithelium itself, supporting formation of a pro-cancer stroma with associated active EMT [183,187]. In a separate study, we also reported effects of inhaled fluticasone propionate on vascular remodelling in patients with COPD [187].…”
Section: Angiogenesismentioning
confidence: 98%